Relação entre as formas de fósforo inorgânico, fósforo disponível e material em solos sob a vegetação de cerrado: II - trabalhos em estufa - Mário Braga, José; Defelipo, Braz Vitor (Revista Ceres, 2025)
An experiment was installed in a greenhouse with the objective of studying the relationship phosphorus (inorganic and available fraction form) and the plant, in order to abtain data about plant growth, absorbed phosphorus and relative yield. These parameters were correlated with phosphorus levels before and after the millet (Setaria italica Beauv) harvest.